(untitled) (Actualizaciones en Sida e Infectología, 2025)
Most people living with HIV who can access and take oral anti-retroviral therapy (ART) can enjoy a normal life expectancy. However, stigma (daily reminder of status and fear of disclosure), forgetting and the inconvenience of daily pills remain barriers to successful ART for some people (1). There is significant interest in longer-acting treatment modalities and the first ever complete long-acting (2-monthly) intramuscular injectable regimen for people who are virally suppressed was licensed for use in 2021. It consists of a novel integrase strand transfer inhibitor (INSTI) called cabotegravir, and rilpivirine, a non-nucleoside reverse transcriptase inhibitor (NNRTI). People who take it prefer it to daily oral therapy with high rates of treatment satisfaction and the discontinuation rates are low. The efficacy has been shown to be similar to that of daily oral ART in both clinical trials and clinical practice. However, the genetic barrier to resistance is lower and when virological failure occurs, single or dual class resistance is very common (2). Providing 2-monthly injections is labour-intensive for clinicians and uptake has not been as high as expected, mainly because it is not presented as an option universally. Data of off-license use in people who are not-virally suppressed are limited.